A relação profissional-usuário na Atenção Primária à Saúde em Belo Horizonte: um estudo sobre a violência nas Unidades Básicas de Saúde - Tatiane Caetano (2015)
Violence at work, specially the work in healthcare, has been reaching alarming proportions every day, not only impacting the life and health of workers to varying degrees, but also affecting their physical, emotional, moral or spiritual integrity, constituting, as a result, an important public health problem. The Primary Health Care (PHC), as the health system gateway, offers services that are preferably located in areas of great social vulnerability, catering to every type of demand from the differentsocial groups. Also, it deals with a diverse clientele, often composed by psychiatric patients, intravenous drug users, among others. The PHC workers are likely to be subjected to violence in their daily work. This work aimed to analyze the professionaluser relationship in the PHC located in the municipality of Belo Horizonte, with regard to violence. This is a qualitative and exploratory research of case study type, whichused the semi-structured interview as a tool for data collection. Key informants were 22 professional members of the Family Health Programme team. The data were collected in three Health Centers of Belo Horizonte, placed in different areas of social and health risk, according to Health Vulnerability Index used in the municipality. Thedata were organized into categories: perception of the work in the Family Health Programme, professional-user relationship in the PHC; violence committed by users; expulsion as a result of violence; feelings related to the situation experienced; ways to deal with violence. The results have shown that the PHC professionals in Belo Horizonte are exposed to different types of violence: verbal aggression, threat, intimidation, bullying and sexual harassment, the most common being the verbal aggression; Professionaluser relationship is expressed in different ways; There islittle absenteeism as a result of violence; The workers have presented mixed feelings towards the violence they suffer, as well as different ways to deal with it.